Effectiveness of simple intuitive formulation to predict thermal post-buckling behavior of symmetric linearly tapered columns - Venkateshwarlu, N.; Akella, Suresh; Reddy, T. Kishen Kumar; Rao, G. Venkateswara (Journal of Structural Engineering, 2024)
Evaluation of thermal post-buckling behavior of heated slender, symmetric, linearly tapered columns, is demonstrated by using a simple intuitive formulation which requires only the mechanical equivalent of the thermal buckling, and the tensile loads, induced in the tapered columns, respectively. Thermal buckling occurs because of the induced compressive load due to the temperature rise from the stress free temperature, when the ends of the tapered columns are constrained to move axially. When the deflections are moderately large, the axial strain-displacement relation becomes nonlinear (von-Karman type). Hence, a tensile load is induced in the column while bending, as a result of the axial boundary conditions, due to the stretching of the neutral axis. Symmetric hinged-hinged and clamped-clamped linearly symmetric tapered columns are considered in this study, so that the structural system becomes completely symmetric. Numerical results in the form of the ratios of thermal post-buckling to buckling loads, varying with the taper and central deflection ratios, obtained from the intuitive formulation, are presented for tapered columns, with the aforementioned boundary conditions. The results match well with those obtained by the Rayleigh-Ritz method, establishing the effectiveness of the intuitive formulation.